Keaktifan Belajar Siswa Ditinjau Dari Metode Pembelajaran Guru Dan Kelengkapan Fasilitas Sekolah Pada Mata Pelajaran Ekonomi Kelas XI di SMA Batik 2 Surakarta Tahun Ajaran 2016/2017 - Sari, Dyah Ayu Novieta, Dr. Djalal Fuadi, MM (2017)
This research is quantitative research. The study population was all students of class XI IS (Social Sciences) in SMA Batik 2 Surakarta academic year 2016/2017, amounting to 157 students. Samples taken as many as 113 students. Mechanical pengemabilansempel conducted by random sampling. The data collection technique using a questionnaire that has been tested beforehand and test validity and test realiabilitas. The data analysis technique used is multiple regression analysis, t-test, F, R^2test, as well as the relative contribution and effective. Based on the results of multiple regression analysis obtained the following results: 1) Y = 1,456 + 0,622X_1+ 0,338X_2 2) From the results obtained t_hitungtest for variables Learning Method Teachers and Educational Facilities Completeness of 6.449 while t_tabelof 1,982. Completeness variable t_hitung for facilities Students' Learning to activeness of 3.849 whilet_tabelof 1,982. 3) From the test results obtained FF_hitungamounted to 188,4>F_tabel = 3.079. Based on the analysis and discussion can be concluded that: 1) variable and Fittings Learning Method Master School Facilities have to activeness Subjects Student in Economics. 2) Ho denied that there is influence that significance to the activeness Learning Method Master Student in Economics Lesson. Ho denied that there is influence that significance to the liveliness Completeness School Facilities Students on the Subject of Economics. 3) Ho is rejected so that together there is influence that significance Teacher Learning Method (X1) and Completeness of School Facilities (X2) on the activeness Student (Y). X1 provides the relative contribution of 63.5% and the effective contribution of 49.2%, X2 gives the relative contribution of 36.5% and the effective contribution of 28.2%. The calculation result obtained 0.774R^2 means that 77,4% of liveliness Student in Economics Subjects affected by Learning Method Master and Completeness of School Facilities, the remaining 22,6% influenced by variables outside the research.